2003
DOI: 10.1300/j125v11n04_03
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Ethnic Agencies

Abstract: Ethnic agencies are important components of multicultural community systems, providing vehicles for community empowerment and self-determination in communities of color. Based on data from a qualitative study of emerging ethnic agencies, this paper explores the communities-building activities of ethnic agencies, describes the characteristics of ethnic agencies that position them to be effective in building communities, and describes what emerging agency leaders perceive they need in order to strengthen their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…When looking at more organization-wide research (as opposed to intervention programs), features of culturally specific service organizations include the following: hiring staff from the same ethnic and linguistic community as service users, include community practices in supporting the individual, engaging in community development to increase cultural pride, decrease isolation and exclusion, encourage cultural consciousness, build power, address issues of racism, locate services in the community and offer holistic programming (Gillam, 2009;Uttal, 2006;Holley 2003). Gillam (2009) also describes culturally specific services as collaborating with service users to design services, resulting in higher user satisfaction.…”
Section: The Research Evidence Of the Benefits And Challenges Of Cultmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking at more organization-wide research (as opposed to intervention programs), features of culturally specific service organizations include the following: hiring staff from the same ethnic and linguistic community as service users, include community practices in supporting the individual, engaging in community development to increase cultural pride, decrease isolation and exclusion, encourage cultural consciousness, build power, address issues of racism, locate services in the community and offer holistic programming (Gillam, 2009;Uttal, 2006;Holley 2003). Gillam (2009) also describes culturally specific services as collaborating with service users to design services, resulting in higher user satisfaction.…”
Section: The Research Evidence Of the Benefits And Challenges Of Cultmentioning
confidence: 99%
“…They stretch themselves to be more The community has been involved in creating the service, helping to design its elements and being involved in correlated activities. We know from the literature (Gillam, 2009;Holley, 2003) In social work practice, these facilitate the creation of relationship that continues to be the essential feature of the ways that clients value social work services.…”
Section: The Literature: Seven Assets Of Culturally Specific Servicesmentioning
confidence: 99%
“…The literature in this area is thin, yet illuminates some promising features of culturally-specific organizations, known sometimes in the literature as "ethnic agencies" (Holley, 2003;Iglehart & Becerra, 1996), or in Canada as "ethno-cultural organizations" (Hansson, Tuck, Lurie, & McKenzie, 2010). The literature review is organized in the following way: beginning with the benefits that have been identified as accruing to clients, then moving to the accountability practices, and then moving into community benefits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ways some of the community benefits have been measured include the following: hiring staff from the community and those who speak their language, include community practices in supporting the individual, engage in community development to increase cultural pride, decrease isolation and exclusion, encourage cultural consciousness, build power, address issues of racism, locate services in the community and offer holistic programming (Gillam, 2009;Holley 2003;Uttal, 2006). They are also more likely than mainstream organizations to provide such benefits.…”
Section: Community Outcomes: Community Development and Systemic Advocacymentioning
confidence: 99%
See 1 more Smart Citation